Representasi Tokoh Mistis Sundel Bolong pada Iklan Pocari Sweat Edisi Ramadan 2025 - Nadiva Aiszhabella; Alvian Alrasid Ajibulloh (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the representation of the figure of the prolific sundel in the 2025 version of Pocari Sweat #IONTahanBocor advertisement using Roland Barthes' semiotic approach. The ad features a local mystical figure sundel bolong in an unusual humorous narrative to convey an educational message about the importance of staying hydrated during fasting. This study uses a descriptive qualitative method with a constructivist paradigm and analyzes visual impressions based on three layers of Barthes' meaning: denotation, connotation, and myth. The results of the analysis showed that the sundel bolong was shown as a figure who was dehydrated and then recovered after consuming Pocari Sweat, which is interpreted as a symbolic form of loss and recovery of body fluids. This representation shows a shift in meaning from a creepy figure to a funny and educational figure. Visual symbols such as the body leaking and the transformation into a cactus reinforce the educational message about hydration that is popularly packaged and lightweight. These findings suggest that advertising not only becomes a promotional medium, but also builds new myths through the construction of popular culture and visual communication.